Fotografía en América Latina : imágenes e identidades a través del tiempo y el espacio - Cánepa Koch, Gisela, 1964-; Kummels, Ingrid (Arte y sociedad (Lima, Peru), 2020)
Historical photographs taken in Latin America have shown their value as crucial sites for the politics of memory, ethnographic imagination and the negotiation of identity. This volume opens a set of questions related to the contemporary agency of this type of images, as well as their current appropriation through new technologies.